PERANAN INFORMASI HARGA POKOK PRODUKSI DALAM PENETAPAN HARGA JUAL BERDASARKAN PRODUKSI SECARA PROSES - Adawia, Popon Rabia (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2014)
Currenly manufacturing industry is very competitive. Manufacturing companies produce their products with purpose to obtaining a maximum profits. Providing quality products to their customers in compete prices but still contributes a significant profit for the company. In manufacturing company, profit is influenced by selling price and cost of production. Cost of production is  consist of  material cost, labour cost, overhead cost, marketing and administration cost. Inaccuracies in calculating cost of production can mistakes in determining of selling price. Cost of production will ascendant to desired profit that acquired of selling price. Manufacturing companies produce their products through mass production, it will collect their costs to use process cost method. By using process cost method will known how much cost of production used so that can calcutaled the selling price as base on to earn desired profit.  Keywords: cost of production, selling price, profit, process cost method